Analysis of Overcurrent Safety in Miniature Circuit Breaker with Alternating Current - Jamaaluddin Jamaaluddin; Izza Anshory; Shazana Dhiya Ayuni (Universitas Muhammadiyah Yogyakarta, 2021)
In the utilization of solar energy, the equipment used includes Photovoltaic Cells, solar charging controls, batteries, protection devices, and other measuring devices. This solar power generation system is the name of a system that can convert solar energy into electric power. This solar power plant used in buildings is referred to as the Solar Building System (SBS). To perfect this solar power generation system, it is necessary to manage the electric power protection system. The protection system in this solar power plant includes the use of Miniature Circuit Breakers (MCB). This Miniature Circuit Breaker is a tool for overcurrent protection in alternating current systems and direct current systems. In order to obtain a good protection system for this solar power plant, a study was conducted on the use of a miniature circuit breaker that is effective for a certain type of current. The research method used is the use of alternating current and direct current miniature circuit breakers in alternating current circuits. Observations and recordings were carried out, so that the obtained results were quite significantly different in their use. From the results of the study, it was found that the Miniature alternating current circuit breaker has better characteristics in alternating current circuits, when compared to direct current miniature circuit breakers.